Methamphetamine and neuroHIV suppress astrocytic potassium channel function in the medial prefrontal cortex via different mechanisms - Chen, Lihua; Cassoday, Stefanie L.; Mamede, Joao I.; Al-Harthi, Lena; Hu, Xiu-Ti (Frontiers in Pharmacology, 2025)
IntroductionMethamphetamine (Meth) is a highly addictive psychostimulant that disrupts neuronal function in the medial prefrontal cortex (mPFC), inducing Meth use disorders (MUD). MUD is often complicated by HIV-associated neurocognitive disorders (HAND, a.k.a. neuroAIDS/neuroHIV), and vice versa. MUD and neuroHIV also disrupt astrocytes, altering their role in supporting normal neuron function. The mechanism(s) underlying Meth and neuroHIV’s impact on astrocytes and astrocyte-neuron interplay remains unknown.MethodsTo define that, we assessed the activity of cortical astrocyte K+ channels that regulate extracellular K+ homeostasis ([K+]e), and substantially neuronal excitability in the brain. HIV-1 transgenic (Tg) rats, a rodent model of neuroHIV with combined antiretroviral therapy (cART) that have no active HIV-1 replication but expression of viral proteins, were given daily repeated Meth administrations. Saline-pretreated non-Tg rats served as control. We then conducted electrophysiological assessment in mPFC astrocytes after acute Meth (20, 100 μM in bath) or daily repeated Meth administrations (5 mg/kg/day s.c. for 5 days) followed by a 3-day withdrawal.ResultsWe found that both Meth and neuroHIV suppressed the activity of astrocytic K+ channels, regardless of subtypes. The maximum reduction occurred in response to combined Meth/neuroHIV, showing exacerbated astrocyte dysfunction. Blocking the trace amine-associated receptor 1 (TAAR1)/G protein-coupled signaling pathway abolished Meth-induced, but not neuroHIV-induced, suppression of K2P, Kv, and Kir channel activity.DiscussionCollectively, these findings demonstrate that Meth and neuroHIV inhibit astrocyte function, which could exacerbate mPFC neuronal dysfunction in MUD and/or neuroHIV. They also suggest that Meth- and neuroHIV-induced astrocytic K+ channel function was mediated by TAAR1-and/or chemokine receptor-coupled signaling pathways.